2011
DOI: 10.21608/jappmu.2011.83334
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Broiler Chicks Affected by Dietary Supplementation With Commercial Enzymes or Probiotics

Abstract: The present study was carried out to investigate the effect of using graded levels of Bio-Nutra 200 and Natuzyme with plant protein diets on the performance of broiler chicks. three dietary levels (0.25, 0.50 and 0.75g/kg) of either Bio-Nutra 200 (probiotic) or Natuzyme (enzyme preparation) in addition to the control without supplementation were used. Therefore, seven experimental diets were formulated to have similar crude protein and metabolizable energy contents during both starter and grower periods. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the present study, Dietary supplementation of deferent levels of commercial probiotics (Provilcc) had a significant effect on carcass yield, and weight of front parts (FP), hind parts (HP), liver and Gizzard compared with the control once (Table 3). Similarly, explained by Novak et al (2011) and Ismail et al, (2011) who indicated significantly better carcass yield, and breast and thigh meat weights. However, contrasting studies were uncovered that dietary probiotic botched to increase carcass yield of chicks fed probiotic-added diets (Pelicano et al, 2005;Karaoglu and Durdag, 2005).…”
Section: Yield Of the Carcassmentioning
confidence: 54%
See 1 more Smart Citation
“…In the present study, Dietary supplementation of deferent levels of commercial probiotics (Provilcc) had a significant effect on carcass yield, and weight of front parts (FP), hind parts (HP), liver and Gizzard compared with the control once (Table 3). Similarly, explained by Novak et al (2011) and Ismail et al, (2011) who indicated significantly better carcass yield, and breast and thigh meat weights. However, contrasting studies were uncovered that dietary probiotic botched to increase carcass yield of chicks fed probiotic-added diets (Pelicano et al, 2005;Karaoglu and Durdag, 2005).…”
Section: Yield Of the Carcassmentioning
confidence: 54%
“…Probiotics is a live microbile feed addition which benefits the host poultry by humanizing it's intestinal tract balance (Ismail et al,. 2011 andAbo El-Maaty et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained (Table 8) revealed that significant differences in Hct, TP, Alb., Hb, lipase, amylase and TAC values between supplemental groups and control. In the line of our study, Ismail et al (2011) revealed that Hubbard broiler chicks fed either feed additives or Natuzyme® supplemented diets achieved significantly higher total protein and albumin levels which may be attributed to the favorable environment in the intestinal tract created by the feeding of these additives, in addition it might have helped to digest and absorb more nitrogen (Mohan et al, 1995 andPanda et al, 2006). Hemoglobin values increased in treated groups (four and three) than control group, this result may be due to addition of these additives might have stimulated iron absorption and activity of the hematopoietic organs and causes erythropoiesis, also high environmental temperature may have influenced the hematological parameters (Hasan et al, 2015).…”
Section: Blood Parametersmentioning
confidence: 66%